A meditação do yoga melhora a qualidade objetiva e subjetiva do sono dos profissionais de saúde - Guerra, Priscilla Caetano [UNIFESP] (2019)
Study Objectives: Healthcare specialists are exposed to several occupational stressors that may contribute to a decreased quality of sleep and can negatively affect psychological functioning. We hypothesised that Yogic meditation may improve objective and subjective sleep quality of these professionals. Methods: 64 healthy professionals were enrolled in a clinical trial (age 35.8 years, 84.4% females, 51.1% physicians). Subjects were randomised into a 30-min Yogic meditation class was held weekly for eight weeks Meditation group (MG, n=32) or Control group (CG, n=32). Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale (ESS), Polysomnography (PSG) were determined at baseline and after eight weeks. Results: Subjects in both groups had similar demographic characteristics. PSQI overall score was significantly lower (p=0.024) in the MG. Reported sleep latency had significant decreased (p=0.046) in the MG at eight weeks compared to baseline. MG had reported sleep latency significantly lower than the CG at eight weeks (p=0.028).The ESS did not show significant differences between the groups and no significant time effect. PSG showed a significant time effect (p=0.020) in decreasing the minutes of wake after sleep onset in the MG at time 2 compared to time 1. Heart rate decreased significantly (p= 0.001) in GM at eight weeks compared to baseline. The GM presented significantly lower heart rate than the CG at eight week (p= 0.035). Conclusion: Yogic meditation may be used as an integrative health tool to foster improvements in sleep related aspects of healthcare professionals.